Layered Double Hydroxides as Systems for Capturing Small-Molecule Air Pollutants: A Density Functional Theory Study - Elaheh Mohebbi; Cristina Minnelli; Eleonora Pavoni; Laura Sisti; Emiliano Laudadio; Pierluigi Stipa (Molecules)
Air pollutants are usually formed by easily spreading small molecules, representing a severe problem for human health, especially in urban centers. Despite the efforts to stem their diffusion, many diseases are still associated with exposure to these molecules. The present study focuses on modeling and designing two-dimensional systems called Layered Double Hydroxides (LDHs), which can potentially trap these molecules. For this purpose, a Density Functional Theory (DFT) approach has been used to study the role of the elemental composition of LDHs, the type of counterion, and the ability of these systems to intercalate NO2 and SO2 between the LDH layers. The results demonstrated how the counterion determines the different possible spacing between the layers, modulating the internalization capacity of pollutants and determining the stability degree of the system for a long-lasting effect. The variations in structural properties, the density of states (DOS), and the description of the charge transfer have been reported, thus allowing the investigation of aspects that are difficult to observe from an experimental point of view and, at the same time, providing essential details for the effective development of systems that can counteract the spread of air pollutants.